Bone metabolism during methylprednisolone pulse therapy in rheumatoid arthritis. - Bijlsma, J W (1986)
The deleterious effects of corticosteroids (CS) on bone are well known, but probably differ depending on duration and dosage of CS therapy. Presently huge amounts of CS are given over a short period of time in different rheumatic conditions. Not much is known about the effect of this kind of CS treatment on bone metabolism. Twenty patients with persistently active rheumatoid arthritis were treated with 1 g methylprednisolone (MP) three times on alternate days over a five day period. Twenty four hours after the first MP pulse serum calcium was increased and the values of parathyroid hormone and 1,25-dihydroxyvitamin D tended to increase. After the second MP pulse, however, these values had returned to the starting values. The urinary calcium excretion increased during MP pulse therapy and returned to the initial value immediately after the pulse therapy. The hydroxyproline excretion tended to decrease during therapy and stayed decreased immediately afterwards, indicating a decrease in bone resorption. It is concluded that bone metabolism is not seriously affected during MP pulse therapy.